Kearns-Sayre syndrome "plus": classical clinical findings and dystonia - MARIE SUELY K.NAGAHASHI; CARVALHO ALZIRA A.S.; FONSECA LUIZ FERNANDO; CARVALHO MARY S.; REED UMBERTINA C.; SCAFF MILBERTO (Arquivos de Neuro-Psiquiatria)
We present a boy of eight years of age with symptoms of Kearns-Sayre syndrome (KSS) characterised by ophthalmoparesis, palpebral ptosis, mitochondrial myopathy, pigmentous retinitis, associated to short stature, cerebellar signs, cardiac blockade, diabetes mellitus, elevated cerebrospinal fluid protein concentration, and focal hand and foot dystonia. The skeletal muscle biopsy demonstrated ragged red fibers, cytochrome C oxidase-negative and succinate dehydrogenase-positive fibers. The magnetic resonance imaging showed symmetrical signal alteration in tegmentum of brain stem, pallidum and thalamus. Mitochondrial DNA analysis from skeletal muscle showed a deletion in heteroplasmic condition. The association of dystonia to KSS, confirmed by molecular analysis, is first described in this case, and the importance of oxidative phosphorylation defects in the physiopathogenesis of this type of movement disorder is stressed.